Intervention to promote preventive dental care for older Korean-American Medi-Cal enrollees in Los Angeles - Yuri Jang; Juyoung Park; Chaeyoon Park; Shinyi Wu; Piedad Suarez-Durall; Soondool Chung; Miyong T. Kim (BMC, 2024)
Abstract Background In California, preventive dental care is covered by Medi-Cal (California's Medicaid program). However, many beneficiaries do not use their dental benefits. Given that a lack of knowledge about oral health and insurance coverage contributes to this underutilization, promoting the use of dental benefits among eligible individuals via an educational program is imperative. Responding to the particular needs of older immigrants with limited English proficiency, we developed a digital oral health intervention for older Korean-American Medi-Cal enrollees in Los Angeles. This educational intervention is designed to be delivered via computers and the Internet. It consists of a 15-min self-running PowerPoint presentation narrated in Korean with links to additional information on the Internet. The slides contain information about the basic etiology of oral diseases, oral hygiene, common myths about oral health and dental care, Medi-Cal coverage of preventive dental care, and how to find a dental clinic. Methods We pilot tested the intervention with 12 participants to examine its feasibility and acceptability. We also obtained participants' qualitative feedback about the intervention. Results A post-intervention quantitative assessment yielded high participant satisfaction and improved oral health and dental care knowledge. Participant responses to the intervention yielded four themes: (1) content and structure, (2) linguistic and cultural aspects, (3) delivery mode, and (4) additional concerns and suggestions. Conclusions Our findings confirm the intervention's feasibility and acceptability and suggest further refinement.